2007
DOI: 10.1080/00952990601091192
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Religious Affiliation in Alcohol Use Among Adolescents in Trinidad, Tobago, and St. Lucia: A Follow-Up Study

Abstract: This finding supports the existing research in Trinidad and developed countries on the effect of various religious denominations of alcohol use and attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In one recent report, the infl uence of religious affi liation was studied in adolescents in Trinidad, Tobago, and St. Lucia. Hindu adolescents were found to have higher levels of regular alcohol use (Rollocks and Dass, 2007). In that study, there was no speculation on the reason that Hindu adolescents were more likely to use alcohol.…”
Section: Discussionmentioning
confidence: 74%
“…In one recent report, the infl uence of religious affi liation was studied in adolescents in Trinidad, Tobago, and St. Lucia. Hindu adolescents were found to have higher levels of regular alcohol use (Rollocks and Dass, 2007). In that study, there was no speculation on the reason that Hindu adolescents were more likely to use alcohol.…”
Section: Discussionmentioning
confidence: 74%
“…For example, Rollocks and Dass (2007) reported differences for various adolescent religious groups in their first and current use of alcohol. These findings suggested that it was the Roman Catholic adolescents who reported a higher tendency toward first and current alcohol use as compared to the other religious groups, with Muslims reporting the lowest tendency toward first and current alcohol use.…”
Section: Religious Affiliationmentioning
confidence: 95%
“…This diversity has the potential to differentially impact youth outcomes. Specifically, outcomes that have been shown to vary as a function of religious affiliation including alcohol use [32,[40][41][42][43], general well-being and death anxiety [44], and childhood behavioral problems [45]. It is also possible that the relationship between religiosity and youth functioning differs as a function of specific religious affiliation (i.e., a moderating effect); however, no studies were located that tested this notion.…”
Section: Placing Religiosity In Cultural-religious Contextmentioning
confidence: 99%